Space Organisation, Creativity and Entrepreneurship: Selected Issues - Anna DĘBICKA; Karolina OLEJNICZAK; Katarzyna SŁUCHOCKA (Communications of International Proceedings, 2021)
In recent years, researchers have become increasingly interested in organising creative spaces. The results of the research suggest that workplace design drives employees’ creativity and innovation. A discussion of the impact of space organisation on the development of creative skills in educational environments is still under development. The aim of this article is the attempt to capture the relationship between the organisation of space and students’ creativity. First, we focus on the definitions of creativity and its place in entrepreneurship theory. Next, we concentrate on the principles of creative space organisation and present some examples from practice. Finally, we demonstrate the conclusions of our research.
Keywords: Entrepreneurship; Creativity; Organization of architectural space